PADLET PLATFORM PRESENT TO ANSWER STUDENTS' LEARNING NEEDS FOR DIGITAL LEARNING - Prasetyo, Adirasa Hadi; Maulidi , Mohammad Rizky; Rofiqi, Moh. Ainor; Agustin, Purnama (As-Sulthan Journal of Education, 2024)
This research examines how the Padlet platform present as a solution to meet students' digital learning needs in the modern era. Using a systematic literature review method, this research analyzes various sources from nationally accredited journals published between 2019-2024. The research results show that Padlet plays an important role as a collaborative platform that provides interactive virtual learning spaces, enables sharing of multimedia content, and supports real-time collaboration between students and teachers. This platform has advantages in terms of ease of use, accessibility from various devices, and the ability to create a dynamic learning environment. Despite limitations in terms of dependence on an internet connection, Padlet remains an effective solution for modern digital learning. This research concludes that Padlet successfully integrates students' digital learning needs through features that support interactive multimedia content, online collaboration, and an effective feedback system, thereby providing a richer and more meaningful learning experience for students in the digital era.